Community Empowerment Design Through the Pentahelix Model in Tourism Development - Afandi, Heru; Rahayu, Nurul Widyawati Islami; Rokhim, Abdul (Eastasouth Institute, 2024)
The tourism sector has become a development sector that has really developed in recent years. Tourism development has three dimensions of development, namely government, academics and entrepreneurs, but this model is modified into five dimensions, namely government as regulator, academics as conceptualizer, tourism business as investor, community working in the tourism sector as accelerator and media as catalyst. These five dimensions are called the pentahelix model. Through this model, it is hoped that the tourism sector can contribute to the community's economy through an empowerment process. So this research aims firstly, to explore tourism development using the pentahelix model, secondly, to design community empowerment using tourism development using the pentahelix model. This goal was achieved with a qualitative approach, a type of case study on Ijen Geopark Bondowoso tourism. This location is one of the biggest tourist attractions in Bondowoso. Data was collected by means of observation, interviews, documentation and FGD. Data were analyzed using descriptive and interpretive techniques and the validity of the data was tested using triangulation of sources and techniques. This research results, firstly, tourism developed using the pentahelix model is more successful than that developed using the triple helix model, because the dimensions used are more comprehensive, secondly, the community empowerment design through the pentahelix model is comprehensive and can absorb a high level of participation in tourism development. Thus, people's income has increased and unemployment has decreased in the Ijen Geopark tourist area because the community participates in tourism development. So, this pentahelix model can be used in designing sustainable community empowerment.